The screening of spring barley varieties with various ecological and geographical origins - E. G. Filippov; A. A. Dontsova; D. P. Dontsov; E. A. Ternovaya; A. S. Vitkovskaya; E. S. Doroshenko (Зерновое хозяйство России)
Barley is one of the main agricultural crops which is widely used in agriculture. The crop has been cultivated since tillage started. Nowadays the purpose of the selection of barley varieties is to improve the quality and nutrients of grain, its forage advantages and technological properties. But it’s necessary to look for and study all new samples of the collection of ARIPB and other institutions to combine all essential traits in one variety. The breeding of new varieties can become successful only if genetically various initial materials that determine advantages and disadvantages of future varieties are available and widely used. The purpose of our study was to assess economically valuable traits of the collection of spring barley varieties. The study was conducted in the fields of the laboratory for barley breeding and seed-growing in FSBSI “Agricultural Research Center ‘Donskoy” (the years of 2014-2016). 167 varieties and samples of spring barley have been studied. The varieties with a complex of valuable traits and properties have been selected. The varieties ‘Manych 121’ (ARRIGC, Russia) and ‘Odessky 22’ (OSSI, Ukraine) possess a shorter period of vegetation than the standard variety ‘Preazovsky 9’ (2 days shorter). The productivity of the variety ‘Zernogradsky 203’ (ARRIGC, Russia) was 6.5 t/ha (the largest one), the variety ‘Bin’ (Sverdlov region, Russia) produced 6.7 t/ha, the variety ‘Rakhat’ (Tatarstan) produced 6.9 t/ha and the variety ‘Gonar’ (Belarus) produced 6.7 t/ha. The varieties ‘Zernogradsky 35 (Rostov region, Russia), ‘Zernogradsky 73’ (Rostov region, Russia), ‘Talovsky 9’ (Voronezh region, Russia), ‘Kamyshinsky 23’ (Volgograd region, Russia), ‘Chelyabinsky 96’ (Chelaybinsk region, Russia), ‘Дзiвосны’ (Belorus), ‘Gonar’ (Germany) and ‘Viking’ (Germany) possess the largest amount of protein in kernels (more than 13.0%).